2017
DOI: 10.1515/jtim-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of survival following percutaneous biliary drainage for malignant biliary obstruction

Abstract: Background and Objectives: Percutaneous transhepatic biliary drain is an intervention used to relieve malignant biliary obstruction. This study aims to explore survival after biliary drain insertion, predictive factors of survival and effectiveness to reduce total bilirubin level. Methods:We conducted a retrospective analysis of 72 patients who had malignant biliary obstruction and received biliary drain during the time period between March 2005 and February 2015. Results: Median patients' age was 56 years. 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Pancreatic, gallbladder and bile duct neoplasia are the most common causes of malignant biliary obstruction (MBO) 1 . In cases of advanced unresectable cancer, the prognosis is poor, and a recent study reported a median survival post-biliary drain insertion of 46 days, with 1-, 3-, and 6-month survival rates of 64.7 %, 26.5 %, and 7.4 % respectively 2 . In these cases, biliary decompression with placement of an endoscopic or percutaneous stent is a critical form of palliative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic, gallbladder and bile duct neoplasia are the most common causes of malignant biliary obstruction (MBO) 1 . In cases of advanced unresectable cancer, the prognosis is poor, and a recent study reported a median survival post-biliary drain insertion of 46 days, with 1-, 3-, and 6-month survival rates of 64.7 %, 26.5 %, and 7.4 % respectively 2 . In these cases, biliary decompression with placement of an endoscopic or percutaneous stent is a critical form of palliative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Tuqan et al, in their study of 72 patients of MBO who underwent percutaneous biliary drainage observed survival rates of 64% and 27% at 1 month and 3 months, respectively. 15 Rees et al, in their study population of 16822 patients with unresectable MBO reported 7-day and 30-day mortality of 5.2% and 23.1%, respectively, with a median survival of 92 days. 16 The factors favoring survival with statistically significance in our study were younger age and good performance status.…”
Section: Discussionmentioning
confidence: 92%
“…Available literature suggests that PTBD is a palliative procedure and does not significantly prolong the patient's life, even though improvement in bilirubin levels can be dramatic [12,13,15,16]. Further, a group of patients do become eligible for additional CT [4,15,17].…”
Section: Discussionmentioning
confidence: 99%